2013
DOI: 10.1136/heartjnl-2012-303585
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the epidemiology, outcome, and prevention of myocardial infarction and stroke in sub-Saharan Africa

Abstract: The early part of the new millennium witnessed reports of a growing burden of cardiovascular disease in Sub-Saharan Africa (SSA). However the contribution of ischemic heart disease and stroke to this increasing burden relative to that caused by hypertensive heart disease, cardiomyopathy and rheumatic heart disease was not clear. Over the last decade, data from the continent has begun to clarify this issue and suggests three main points. The burden of ischemic heart disease relative to other causes of heart dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 68 publications
(78 reference statements)
0
39
0
1
Order By: Relevance
“…A risk factor is defined as an attribute, characteristic or exposure of an individual which increases the likelihood of developing a disease or injury [38,39]. Overall, only 15.63% adults in the study population were free of any self -reported risk factor while risk factor was selfadmitted in 84.37% (one risk factor -32.71%, two -43.12%, above two -8.54).…”
Section: Discussionmentioning
confidence: 99%
“…A risk factor is defined as an attribute, characteristic or exposure of an individual which increases the likelihood of developing a disease or injury [38,39]. Overall, only 15.63% adults in the study population were free of any self -reported risk factor while risk factor was selfadmitted in 84.37% (one risk factor -32.71%, two -43.12%, above two -8.54).…”
Section: Discussionmentioning
confidence: 99%
“…[16,17] There are limited data regarding ACSs in the SA context, with observational data suggesting that there are high intervention rates and frequent use of evidencebased pharmacological therapies with comparative outcomes when compared with international standards. [18] These data reflect mainly the care delivered in the private sector, and do not fully represent care from the public sector where resources are limited and timely presentation to healthcare facilities capable of managing ACSs is often delayed.…”
Section: Acss In Sub-saharan Africamentioning
confidence: 99%
“…2 Despite evidence to suggest that CVD-related mortality rates are increasing in the region, it is only now being recognized as an important public health issue in sub-Saharan Africa, with coronary artery disease shown to rise in incidence in sub-Saharan Africa. 3,4 Cardiovascular diseases are the main noncommunicable conditions in SSA and now 9.2% of total deaths in the African region are caused by CVD, 5 being the leading cause of death in the population aged over 45. 6 Cardiovascular diseases account for 7-10% of all adult medical admissions to hospitals in Africa, with heart failure contributing to 3-7%.…”
Section: Introductionmentioning
confidence: 99%